Endodontic surgery with simultaneous root canal filling: case report - Fernando Accorsi Orosco; Lúcia Coelho Garcia Pereira; Monica Misaé Endo; Ralph Angeli Rangel; Alexandre Silva Bramante; Clóvis Monteiro Bramante (Revista Sul-Brasileira de Odontologia, 2015)
Endodontic surgery is an excellent alternative for solving problems unsolved by conventional treatments and/or root canal retreatment. Objective: This study aims to report a clinical case of an endodontic surgery with simultaneous root canal filling. Case report: The left mandibular lateral incisor (#32) showed constant exudation even after root canal instrumentation and many changes of calcium hydroxide paste as intracanal medication. So, the treatment´s option was the endodontic surgery with simultaneous root canal filling for removing the periapical lesion. After the root canal filling, the curettage and apical plasty were made and the bone cavity was filled with calcium sulfate. Histopathological examination pointed out a periapical cyst. Conclusion: Endodontic surgery with simultaneous root canal filling of the tooth #32 was successful, once the patient did not exhibited any clinical symptoms, the exudate disappeared, and radiographically, it can be observed the formation of bone repair. The time of follow-up was of four months.